An Empirical Study on "Setting Benchmarks in Quality Higher Education' Through Activity Based Learning (Trinity Journal of Management, IT & Media (TJMITM), 2011)
With the advent of !'ewer ~nd mo~em innovative  chnologies in teaching commg up, it has become  ally important for the teachers to shift their focus from  dit/onal to modem method of teaching which is not  /y student friendly but also aimed at practical  penences and hands on tasks. The paper attempts ~o  in an insight into the problems faced by teachers m  faining and reinforcing the students in academic tasks  d inclusion of the curriculum which best matches the responsibilities of the students which they are to take  m the near future. The paper would demonstrate the  ddel for effective and interesting teaching pedagogy  ich is not only enriching but also creating among  dents a thirst for and an appetite for learning by being  olved in it. The research methodology would include  scriptive design and analysis will be made on the  sis of the response by the Faculty and students  rsumg Higher Education. The model of great help for  ovative teaching has also been proposed henceforth.
Keywords: Quality; Innovation; Leaming; Change